ANALYSIS OF CONSUMER BEHAVIOR TOWARDS DIGITAL TECHNOLOGY IN UMRAH RELIGIOUS ECOTOURISM PACKAGES - Sayid Abas; Choirul Hamidah; Asis Riat Winanto (ZILLZELL MEDIA PRIMA, 2025)
Consumer behavior in choosing Umrah and Hajj religious ecotourism packages is increasingly influenced by advances in digital technology. With digital platforms, consumers can now access information, compare prices, and place orders online more easily. This study aims to analyze how digital technology influences consumer decisions in choosing Umrah and Hajj packages and its impact on the religious tourism industry. The methodology of this research will use a qualitative approach to get a comprehensive picture of consumer behavior towards digital technology in choosing Umrah and Hajj religious ecotourism packages, observations, interviews, analysis of supporting documents for pilgrims and Umrah and Hajj travel agencies. As informants, Umrah and Hajj pilgrims who use digital services as a consideration for choosing Umrah packages. The results of the study obtained an idea that consumers interact with digital technology in choosing religious ecotourism packages for Umrah and Hajj, as a preference for the use of technology that influences decisions. Testimonial Reviews, Comfort, Update, Efficiency, Facilities, Wide Network, Price, Convenience, Trust, Decision and Content, are some of the factors that influence decision-making in choosing an Umrah package.